Analysis Of Operational Management Functions In Ud. Aneka Plastic - Nora, Agustalinda; Nurdelila, Nurdelila; Sari Harahap, Diana (CV. Inara, 2022)
UD. Aneka Plastic is wrong one company engaged in the plastics industry. Destination this research is for describe managementoperational with explain function managementoperational on UD. Aneka Plastic. Method study used is qualitative and purposive sampling with conducted interviews with 3 informants. Test validity data which used istriangulation source. Results study this show thatthe company has a capacity that is not excess and could produceproduct in accordance with Requestbuyers, strategic location so easy to reach by supplier and power work, systemlocation which notice security and safety employee,good product quality and difficult for competitors to imitate, as well as method production which clear. Besides that, have scheduling regarding production, namely Master Production Detailed Schedule , Detailed Short-Term Schedule withhave system management maintenance machine,and Staff Schedule which clear so that company could carry out production activities smoothly. Supervisionoperational in company showed with delivery of goods fulfilled, stock storage in sufficient warehouse, have potential suppliers, and could control inventory with good. Structureorganization, job description , vision and mission, as well as SOPs written and clearly required by the company. Motivation, more employee involvement, and rewards are also necessarynoticed for employee. Facility supporter also need added so that atmosphere in company no boring .